Drying behavior and decay resistance of rubberwood from steamed log and presteamed lumber - Rodrigues, Paula Lúcia Martins [UNESP]; Severo, Elias Taylor Durgante [UNESP]; Calonego, Fred Willians [UNESP]; Pelozzi, Melany Maria Alonso [UNESP] (Taylor & Francis, 2018)
The objective of this study was to evaluate the effect of log steaming and steaming prior to drying singly and both treatments together on the drying behavior and decay resistance of Hevea brasiliensis wood (rubberwood). Logs with a diameter of 34.6 ± 4.4 cm were used. Half of the logs were kept in their original condition, and the other half were steamed at 90°C for 36 h. Later, the logs were cut into flat sawn boards. Half of the boards were kept in their original condition, and the other half were presteamed at 90°C for 3 h after 1 h of heating-up. These boards were dried in a drying kiln. The drying defects, drying time, drying rate, and decay resistance of wood to the Pycnoporus sanguineus fungus were determined. The results showed that the steaming is not suitable for decreases in the time and the drying rates of this kind of wood, and it neither reduces the drying defects of boards. Furthermore, these treatments adversely affected the decay resistance of rubberwood to P. sanguineus fungi.
Keywords: Drying defects; Hevea brasiliensis; steamed logs; steaming prior to drying; wood drying